Formation of nutrient regime of soil in the field of sugar beets depending on their fertilization in short-term crop rotation - Цвей, Я. П.; Тищенко, М. В.; Філоненко, С. В.; Ляшенко, В. В. (Scientific Progress & Innovations, 2018)
Optimization of mineral nutrition of plants is one of the most significant means to regulate physiological processes that determine yield formation of any crop. In intensive farming the yield of crops depends on the natural fertility of soil and weather conditions only by 25%. In this case, fertilizers provide from 30 to 60% of the yield, high quality seeds – from 5 to 20%, and plant protection products – from 5 to 15%. Therefore, studying of the optimal provision of sugar beet plants with nitrogen, mobile phosphorus and exchangeable potassium due to the application of various doses of organic and mineral fertilizers is important and relevant, especially for the conditions of the zone of inadequate moisture. The purpose of the research was to determine the influence of sugar beet fertilization on the formation of the nutrient regime of the soil underneath in short-rotation fertile crop rotation. The research task was the study of the effect of various doses of organic and mineral fertilizers, applied to sugar beets, on the content of nitrate and mineral nitrogen, as well as the effect of various fertilization systems used during the cultivation of sugar beets on the content of mobile phosphorus in the field of crop in short-term crop rotation and the study of the content of exchangeable potassium in typical slightly alcanlinized black soil while applying various doses of organic and mineral fertilizers to sugar beets. The following preliminary conclusions can be made based on the data of one-year research: In short-term crop rotation, the highest content of nitrate and mineral nitrogen in the arable soil layer was at the time of germination of sugar beets in the areas where the manure + N90P120K90 was applied in the amount of 50 tons per hectar - 17.2 and 20.1 mg/kg of soil. The application of 50t/ha of manure + N90P120K90provided the largest amount of mobile phosphorus in the arable layer during the period of the crop germination – 80.0 mg/kg of soil, due to the increasing mobility of phosphates from organic fertilizers and a smaller transition of phosphorus in the insoluble compounds. The change of the dose of fertilizers applied to sugar beets from 25 t/ha of manure + N180Р240К180 to 50 t/ha of manure + N90Р120К90resulted in the increase of the content of exchangeable potassium in the arable soil layer during sugar beets germination from 170.0 to 177.0 mg/kg of soil. It is the effect of the application of high dose of organic fertilizers, which after mineralization of manure provided the increase of the content of exchangeable potassium in the soil.